1988
DOI: 10.1111/j.1432-1033.1988.tb14188.x
|View full text |Cite
|
Sign up to set email alerts
|

Reductive cleavage and reformation of the interchain and intrachain disulfide bonds in the globular hexameric domain NC1 involved in network assembly of basement membrane collagen (type IV)

Abstract: The formation of collagen IV dimers in the extracellular space requires the association of two C-terminal globular domains giving rise to a large hexameric structure NC1 (Mr = 170,000). NC1 hexamer was purified from collagenase digests of a mouse tumor and several human tissues. It was shown by electrophoresis to consist of two kinds of cross-linked, dimeric segments, Da and Db (Mr about 50,000), and monomeric segments in a molar ratio of about 3:1. In the native hexamers free SH groups were detectable by N-[1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…In most basement membranes, including the GBM, the NC1 hexamer contains a large proportion of NC1 dimers (ϳ75%) cross-linked by a covalent bond that connects two adjoining protomers in the network. Previously, this cross-link was identified as a disulfide bond (21), but recent crystallographic studies suggested a cross-link between the conserved Met-93 and Lys-211 residues (10). Because each NC1 domain of a protomer can be crosslinked to the corresponding NC1 domain of the opposite protomer, each hexamer is characterized by three NC1 dimers that reflect specific trimer-trimer interactions.…”
Section: Triple Helical and Network Organization Of The ␣3(iv)mentioning
confidence: 99%
See 1 more Smart Citation
“…In most basement membranes, including the GBM, the NC1 hexamer contains a large proportion of NC1 dimers (ϳ75%) cross-linked by a covalent bond that connects two adjoining protomers in the network. Previously, this cross-link was identified as a disulfide bond (21), but recent crystallographic studies suggested a cross-link between the conserved Met-93 and Lys-211 residues (10). Because each NC1 domain of a protomer can be crosslinked to the corresponding NC1 domain of the opposite protomer, each hexamer is characterized by three NC1 dimers that reflect specific trimer-trimer interactions.…”
Section: Triple Helical and Network Organization Of The ␣3(iv)mentioning
confidence: 99%
“…In comparison, the ␣1⅐␣2(IV) network is composed of (␣1) 2 ␣2 protomers (9,10,21), whereas the ␣1⅐␣2⅐␣5⅐␣6(IV) network is composed of (␣1) 2 ␣2 protomers interacting with (␣5) 2 ␣6 protomers (17). Thus, the three known collagen IV networks are assembled from three basic building block protomers with the chain compositions of (␣1) 2 ␣2, ␣3⅐␣4⅐␣5, and (␣5) 2 ␣6.…”
Section: Organization Of Chains Within the ␣3⅐␣4⅐␣5(iv) Network-mentioning
confidence: 99%
“…The cross-links connect ␣1-like monomers (␣1-␣1, ␣1-␣5, and ␣3-␣5) and ␣2-like monomers (␣2-␣2, ␣2-␣6, and ␣4 -␣4) (3,4). For two decades, the reduc-ible dimers were thought to consist of monomers bound by disulfide cross-links (5,6). However, the recent x-ray crystal structures of the NC1 hexamers of bovine lens capsule basement membrane and human placenta basement membrane, determined independently by us (7) and Than et al (8), respectively, have disproved this hypothesis.…”
mentioning
confidence: 99%
“…Subsequent studies of ␣1.␣2, ␣3.␣4.␣5, and ␣1.␣2-␣5.␣6 collagen IV networks have shown that the cross-links connect ␣1-like monomers (␣1-␣1, ␣1-␣5, and ␣3-␣5) and ␣2-like monomers (␣2-␣2, ␣2-␣6, and ␣4-␣4) (9,10). For two decades, the reducible dimers were thought to be disulfide-linked monomers (7,11). However, the recent x-ray crystal structures of the NC1 hexamers of bovine lens capsule basement membrane (LBM) and human placenta basement membrane (hPBM), determined independently by us (4) and Than et al (6), respectively, have disproved this hypothesis.…”
mentioning
confidence: 99%